KAJIAN POTENSI PENGEMBANGAN AGROWISATA KAWASAN GUNUNG SALAK ENDAH - Murdaningsih Murdaningsih; Nina Nurdiana (BUANA SAINS, 2009)
The research about potency of agrotourism development was conducted the first step from agrotourism planning in Gunung Salak Endah Area (GSEA). This research was studied about physical aspects, biological aspects, social aspects and economical aspects. The area appropriate for every agriculture commodity on agrotourism development were agrotourism comprehension; and tourist preference to activity types, agriculture works and facility in agrotourism development were analyzed with chi square. Agrotourism development was coursed to the activities that use agriculture as a tour object and can see the view. Land can used agrotourism development is 418,93 ha with using wet fields A (109,03 ha; wet rice), wet fields B (7,88 ha; wet rice or corn), dry fields A (132 ha; dry rice), dry fields B (22,78 hectare; orange, red pepper, cucumber, papaya, banana or livestock), dry fields C (128,98 hectare; red pepper, long beans, green beans, cucumber, papaya or banana), dry fields D (8,84 hectare; tomato, red pepper, long beans, green beans, cucumber, papaya or banana), calm fishery (9,36 hectare) and flowered plants. The activity form of fishery agrotourism, horticulture and food plant are cultivation whereas for livestock is ranch